2013
DOI: 10.1177/1557988313510731
|View full text |Cite
|
Sign up to set email alerts
|

Developing Weight Management Messages and Interventions for Baby Boomer Men

Abstract: The goal of this study was to explore the weight management experiences of Baby Boomer men (born between 1946 and 1964) and to use the information to develop targeted messages and interventions. Twenty men were interviewed. The Health Belief Model was used as the study's theoretical framework. Men correctly identified health risks of being obese. However, most believed that body mass index and weight charts were unrealistic, and a few felt that they would be too "skinny" at the recommended weight. Wives were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(29 citation statements)
references
References 45 publications
3
25
1
Order By: Relevance
“…The characteristics of the CDPM program itself are important in determining whether men will be motivated to participate. As indicated above, several studies in this review have explored men's perceptions of CDPM programs, many of which noted that men view them as feminine (Coles et al, 2010;Gray et al, 2013;Wirth et al, 2014). In addition, in a survey of men's reasons and preferences for attempting weight loss (n = 72; M age = 44.99, SD age = 11.77), Wolfe and Smith (2002) reported that 52.8% of participants most preferred working individually with a personal trainer, while 34.7% endorsed group exercise.…”
Section: Pull Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…The characteristics of the CDPM program itself are important in determining whether men will be motivated to participate. As indicated above, several studies in this review have explored men's perceptions of CDPM programs, many of which noted that men view them as feminine (Coles et al, 2010;Gray et al, 2013;Wirth et al, 2014). In addition, in a survey of men's reasons and preferences for attempting weight loss (n = 72; M age = 44.99, SD age = 11.77), Wolfe and Smith (2002) reported that 52.8% of participants most preferred working individually with a personal trainer, while 34.7% endorsed group exercise.…”
Section: Pull Factorsmentioning
confidence: 99%
“…In focus groups investigating men's program preferences, Coles et al (2010) identified that programs that were of no cost were most appealing to men. Additionally, Wirth et al (2014) qualitatively examined the weight loss experiences of men (n = 20; M age = 53, SD age = 5.50) for the purpose of designing weight loss messages and interventions, and reported that financial incentives, such as tax credits or participation at no cost, were perceived as facilitators to join programs for many of the men interviewed.…”
Section: Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, there is limited evidence available to inform the design of engaging and effective PA and weight loss interventions for men (Bottorff et al, 2015;George et al, 2012;Young et al, 2012). This study suggests that researchers may increase the effectiveness of their programs by drawing on the psychological (e.g., Olander et al, 2013) and sociological (e.g., Courtenay, 2000;Wirth et al, 2014) literature to create innovative programs that target men's self-efficacy and intention to perform PA. 2. This study suggests that social support and outcome expectations may not be as important to target in PA programs for men, but this hypothesis requires further validation.…”
Section: Recommendations For Researchmentioning
confidence: 99%
“…Even though men report less body dissatisfaction than women do, they still report a degree of body dissatisfaction and a desire to lose weight . Furthermore, as men get older, they place greater value on their health and are more willing to assume more responsibility for their health .…”
Section: Introductionmentioning
confidence: 97%